Growth of graphene with large single-crystal domains by Ni foam-assisted structure and its high-gain field-effect transistors. Issue 3 (2nd January 2019) - Gao, Xuedong; Yu, Cui; He, Zezhao; Song, Xubo; Liu, Qingbin; Zhou, Chuangjie; Guo, Jianchao; Cai, Shujun; Feng, Zhihong
Abstract : Growth of large-domain-sized single-crystal graphene with controlled nucleation density by Ni foam structure. Abstract : High-quality graphene materials and high-performance graphene transistors have attracted much attention in recent years. To obtain high-performance graphene transistors, large single-crystal graphene is needed. The synthesis of large-domain-sized single-crystal graphene requires low nucleation density; this can lead to a lower growth rate. In this study, a Ni-foam assisted structure was developed to control the nucleation density and growth rate of graphene by tuning the flow dynamics. Lower nucleation density and high growth rate (∼50 μm min −1 ) were achieved with a 4 mm-gap Ni foam. With the graphene transistor fabrication process, a pre-deposited Au film as the protective layer was used during the graphene transfer. Graphene transistors showed good current saturation with drain differential conductance as low as 0.04 S mm −1 in the strong saturation region. For the devices with gate length of 2 μm, the intrinsic cut-off frequency f T and maximum oscillation frequency f max were 8.4 and 16.3 GHz, respectively, with f max / f T = 1.9 and power gain of up to 6.4 dB at 1 GHz. The electron velocity saturation induced by the surface optical phonons of SiO2 substrates was analyzed. Electron velocity saturation and ultra-thin Al2 O3 gate dielectrics were thought to be the reasons for the good current saturation and high power gain of the graphene transistors.